The EFFORTS of BAGHDAD SCHOLARS in PROPHET's HADITH and Its SCIENCES at the 14th CENTURY AH - Hussein , Abdulqader (Islamic Sciences Journal, 2023)
The importance of the subject comes from the fact that it has remained almost absent or ambiguous from many, namely that the science of "Prophet's Hadith" in Iraq was faded or obliterated in this century specifically. So the research comes to answer this question and reveal this fact. It comes also to highlight an important era of the history of Baghdad which has not been given sufficient attention in explaining the efforts of its scientists, especially those engaged in the science of "Prophet's Hadith" in both writing and achieving manuscripts. The research was divided into an introduction, a preface, and thirteen sections, as well as a conclusion ending with the most important results. The research method is inductive and descriptive in tracking the efforts of scientists and researchers and their writing and achieving manuscripts works as possible as the availability of resources, and this type of authorship known as (Bibliography). One of the most important results of the research is that the research monitored (162) scientific efforts of the Baghdad scientists in the Hadith and its sciences in "writing and achieving manuscripts, including (108) in writing and (54) in achieving manuscripts. This means that the efforts of authorship are greater than achieving manuscripts efforts of this century. (66.66%) of the total of this scientific output according to the available resources, and this indicates that their obsession of creativity has been stronger. These scientific efforts have been divided among thirteen sections according to the classification of Hadith scholars depending on the available resources. (12.34%) of these efforts related to Baghdad scholars methodology which indicates their attention to this art of classification, and the strength of their methodical thinking based on making their minds busy with explaining their curricula in classifying in addition to its impact on each art, Perhaps this comes from some of the effects of the school of opinion in Baghdad